The Role of Diet and Lifestyle in Women with Breast Cancer: A Review of the Literature - Kamal, Mohamed; Alahmadi, Hussam; Alamri, Ayman; Ozbuk, Ahmed; Beek, Asem; Alharbi, Waleed (International Journal of Innovative Research in Medical Science, 2022)
One in eight women worldwide will develop breast cancer in their lifetime. Obesity, physical activity, and dietary composition are known to influence the prognosis of breast cancer. There have been significant concerns regarding the toxicity of existing pharmaco- and chemotherapies, and additional complementary dietary and lifestyle interventions are suggested for breast cancer prevention. This review aims to highlight current information regarding the association between dietary patterns and lifestyle with BC, including risk and prognosis. In addition, this article discusses dietary intake, physical activity, and other habits as lifestyle modification strategy targets. The incidence of breast cancer is increasing at an alarming rate worldwide, making it the most prevalent malignancy in women. A significant relationship exists between obesity, physical inactivity, a sedentary lifestyle, dietary patterns, and breast cancer risk. Unhealthy lifestyle habits, such as smoking, alcohol consumption, and tobacco use, also contribute to this increased risk. Obese women who have a high risk of breast cancer had better metabolic and inflammatory profiles when they engaged in lifestyle activities and diet interventions that were tailored to their needs. Physical activity was linked with a reduction in cancer incidence and mortality risk. A decrease in an individual’s consumption of red meat, animal fat, and sugary foods, as well as their increased consumption of fiber, fruits, and vegetables, were associated with a reduced risk of breast cancer. Other modifiable risk factors, such as smoking cessation and the avoidance of alcohol and tobacco, contributed to breast cancer survival. A healthy lifestyle that includes exercise and dietary modifications may serve as adjuvants to expedite breast cancer prevention interventions and optimize the health of cancer survivors.